2011
DOI: 10.1021/ol201137v
|View full text |Cite
|
Sign up to set email alerts
|

A [2 + 2] Cycloaddition Dimer and a Diels–Alder Adduct fromAlpinia katsumadai

Abstract: An unusual katsumadain dimer via a [2 + 2] cycloaddition, katsumadain C (1), and a unique chalcone-diarylheptanoid adduct via a Diels-Alder reaction, calyxin Y (2) with novel carbon frameworks, were isolated from the seeds of Alpinia katsumadai. Their structures and relative configurations were determined by spectroscopic evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…Chemical Constituents: Majority of the chemical compounds isolated from genus Alpinia has been shown multiple medical potentials and possess novel chemical structures 58,59 Other than above chemical constituents some glycosides 75 , lignins 76 , phenylpropanoids and volatile oils 77 were found in the genus Alpinia. A new katsumadain dimer named "katsumadain" has been isolated from Alpinia katsumadai 78 . A plant growth inhibitor named dihydro-5, 6dehydrokawain has been isolated from Alpinia speciosa leaves 79 .…”
Section: Morphological Characteristics Of Genusmentioning
confidence: 99%
“…Chemical Constituents: Majority of the chemical compounds isolated from genus Alpinia has been shown multiple medical potentials and possess novel chemical structures 58,59 Other than above chemical constituents some glycosides 75 , lignins 76 , phenylpropanoids and volatile oils 77 were found in the genus Alpinia. A new katsumadain dimer named "katsumadain" has been isolated from Alpinia katsumadai 78 . A plant growth inhibitor named dihydro-5, 6dehydrokawain has been isolated from Alpinia speciosa leaves 79 .…”
Section: Morphological Characteristics Of Genusmentioning
confidence: 99%
“…Several species reported the presence of chalcone dimers bound by a cyclobutane (Figure 2) [29][30][31][32][33][34][35]. The phytochemical study of the roots of Dahlstedtia grandilora was observed, and for the irst time, the occurrence of dimerization in retrochalcones was noted [24].…”
Section: Flavonoids -From Biosynthesis To Human Healthmentioning
confidence: 99%
“…The phytochemical study of the roots of Dahlstedtia grandilora was observed, and for the irst time, the occurrence of dimerization in retrochalcones was noted [24]. The mechanisms of [2 + 2] cycloaddition involved in the formation of these compounds are suggested [30,35]. In spite of the lack of biosynthetic studies of these natural products, much efort has been made in elucidating the biosynthetic pathways of lavonoids from a genetic perspective.…”
Section: Flavonoids -From Biosynthesis To Human Healthmentioning
confidence: 99%
“…We recently reported the biomimetic total synthesis of katsumadain C [7], a natural product isolated from the same resource as katsumadain A and B [8]. As part of our continuous interest in the synthesis of bioactive 2-pyranone-derived natural products, we launched a project aiming to develop a highly efficient route for the synthesis of katasumadain A as well as its analogues, which would pave the way for their application in further biomedical investigations.…”
Section: Introductionmentioning
confidence: 99%